Evaluasi Kualitas Air Sungai Pemurus Kota Banjarmasin Berdasarkan Standar Baku Mutu - Nor Zakia Rahma; Ellyn Normelani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Residential and agricultural pressures along the Pemurus River are suspected to degrade its water quality. This study aims to (1) assess the water quality of the Pemurus River based on the Class II water quality standards stipulated in Government Regulation (PP) No. 22 of 2021 on Environmental Protection and Management, and (2) determine the river’s pollution level using the Pollution Index. A quantitative descriptive method with a cross-sectional approach was employed. Water samples were collected at three observation points using purposive sampling and the grab sampling technique. The analyzed parameters covered physical, chemical, and biological aspects. The measurement results were compared with the Class II water quality standards of PP No. 22/2021 and further evaluated using the Pollution Index to determine the pollution status. The results indicate that temperature, TDS, pH, and nitrate met the required standards, while total coliform significantly exceeded the permissible limit, indicating serious microbiological contamination. The Pollution Index values ranged from 1.90 to 3.26, classifying all sampling points as lightly polluted, with pollution loads increasing from upstream to downstream. These findings highlight the need for pollution control through improved sanitation and better management of domestic wastewater.